The relation of cortisol and sex hormone levels to results of psychological, performance, IQ and memory tests in military men and women - Flegr, Jaroslav; Hampl, Richard; Černochová, Dana; Preiss, Marek; Bičíková, Marie; Sieger, Ladislav; Příplatová, Lenka; Kaňková, Šárka; Klose, Jiří (Neuro endocrinology letters, 2012)
BACKGROUND: Cortisol, along with other hormones of hypothalamo-pituitary-adrenal axis, belongs to one of the main factors influencing psychological and pathognomic factors, intelligence, and memory. METHODS: The aim of our study was to review a large battery of psychological, performance, IQ and memory tests as to their relation with cortisol, testosterone and estrogen levels in groups of 100 men and 93 women who attended the Central Military Hospital in Prague for regular entrance psychological examinations for military personnel. RESULTS: In men, we detected positive correlations between cortisol and emotional lability, and negative correlations with impulsivity, while in women hypochondria and psychopathology were negatively correlated, and aggression measured with the Meili selective memory test had a positive relation to cortisol level. Testosterone correlated positively with emotional liability and negatively with impulsivity in men, and negatively with hypochondria and psychasteny, indirect aggression, irritability and paranoia in women. Estradiol correlated positively with psychopathology in men, and negatively with phobia. It was positively correlated with negativism in women. No clear correlation was observed between the concentration of steroid hormones and psychomotor performance or intelligence. CONCLUSIONS: Concentrations of steroid hormones correlate with results of several psychological tests, the sign and magnitude of these correlations, however, very often differ in military men and women.
Keywords: Humans; Hydrocortisone; ozbrojené síly; paměť; hydrokortison; Female; dospělí; inteligence; Intelligence; Psychiatric Status Rating Scales; lidé; Intelligence Tests; duševní poruchy; Adult; Military Personnel; inteligenční testy; ženské pohlaví; psychiatrické posuzovací škály; Male; Testosterone; estrogeny; Psychomotor Performance; Mental Disorders; Memory; mužské pohlaví; testosteron; psychomotorický výkon; Estrogens